RESEARCH ON ELECTRICAL PRODUCTION OF MULTI-PURPOSE SUSTAINABLE DAMS IN THE WORLD - (:unkn) unknown (Influential Scholarly Research Publication, 2021)
Dams a facility that stores water in the and uses water in a sustainable way. The high use of imported energy resources, which is composed entirely of fossil fuels and which has negative impacts in terms of economic and political aspects, clearly shows that the use and potential of domestic and renewable energy resources is inevitable. Increasing the domestic and renewable primary energy source of hydroelectric energy production to the highest values is only possible with the development of the right tank management policies. Dams also had been built to produce motive power and electricity since the industrial revolution. Development priorities changed, experience accumulated with the construction and operation of dams. Although the importance of water is well known in the human life and civilization around the world, still various groups argue that expected economic benefits are not being produced and that major environmental, economic and social costs are not being taken into account
Keywords: 13. Climate action; 11. Sustainability; 8. Economic growth; 7. Clean energy; 6. Clean water; 12. Responsible consumption